2020
DOI: 10.1111/lam.13412
|View full text |Cite
|
Sign up to set email alerts
|

Ethidium and propidium monoazide: comparison of potential toxicity onVibriosp. viability

Abstract: Significance and Impact of the Study: Ethidium monoazide (EMA) and propidium monoazide (PMA) treatment have commonly been used combined with qPCR to discriminate viable and dead cells. However, these DNA-binding dyes can damage membranes in viable bacteria, generating false-negative results. Most available studies examined either EMA-qPCR or PMA-qPCR, based on the literature to select the dye of interest. However, none of them tested the cytotoxicity of EMA vs PMA on various Vibrio sp. strains. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Currently, PMA dye combined with fluorescent qPCR (PMA-qPCR) is widely used as a rapid detection method in food, medicine, and the environment. It detects not only bacteria, such as E. coli ( Miotto et al, 2020 ; Deshmukh et al, 2021 ), Salmonella ( Techathuvanan and D'Souza, 2020 ), Lactobacillus ( Yang et al, 2021 ), Vibrio ( Copin et al, 2021 ), and Listeria monocytogenes ( Kragh et al, 2020 ), but also fungi, such as C.albicans ( Asadzadeh et al, 2018 ), and even virus ( Zeng et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, PMA dye combined with fluorescent qPCR (PMA-qPCR) is widely used as a rapid detection method in food, medicine, and the environment. It detects not only bacteria, such as E. coli ( Miotto et al, 2020 ; Deshmukh et al, 2021 ), Salmonella ( Techathuvanan and D'Souza, 2020 ), Lactobacillus ( Yang et al, 2021 ), Vibrio ( Copin et al, 2021 ), and Listeria monocytogenes ( Kragh et al, 2020 ), but also fungi, such as C.albicans ( Asadzadeh et al, 2018 ), and even virus ( Zeng et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The traditional pathogenic culture method and immunoassay method are cumbersome, unreliable, and prone to false-negative results, especially in distinguishing homologous strains and VBNC cells. It is necessary to find more accurate detection techniques for V. vulnificus detection (Copin et al, 2021). In recent years, with the development of heat-resistant DNA polymerases (e.g., Taq DNA polymerase) and thermal cycling instruments, molecular biology techniques represented by polymerase chain reaction (PCR) have gradually advanced from the research laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, this bottleneck could be broken by combining photo-reactive DNA-binding dye, such as propidium monoazide (PMA) and ethidium monoazide (EMA), with nucleic acid molecular diagnostics (Codony et al, 2020). A previous study revealed (Copin et al, 2021) that pre-treatment with different concentration gradients of EMA in seafood and environmental samples had a lethal effect on V. vulnificus strain compared with PMA. PMA could penetrate into the damaged and dead cells and selectively bind to the DNA in these cells, which can effectively inhibit their PCR amplification (Elizaquível et al, 2014).…”
Section: Introductionmentioning
confidence: 99%